Activating GENeral practitioners dialogue with patients on their Agenda (MultiCare AGENDA) study protocol for a cluster randomized controlled trial - Altiner, Attila (BioMed Central, 2012)
BACKGROUND: This study investigates the efficacy of a complex multifaceted intervention aiming at increasing the quality of care of GPs for patients with multimorbidity. In its core, the intervention aims at enhancing the doctor-patient-dialogue and identifying the patient’s agenda and needs. Also, a medication check is embedded. Our primary hypothesis is that a more patient-centred communication will reduce the number of active pharmaceuticals taken without impairing the patients’ quality of life. Secondary hypotheses include a better knowledge of GPs about their patients’ medication, a higher patient satisfaction and a more effective and/or efficient health care utilization. METHODS/DESIGN: Multi-center, parallel group, cluster randomized controlled clinical trial in GP surgeries. Inclusion criteria: Patients aged 65–84 years with at least 3 chronic conditions. Intervention: GPs allocated to this group will receive a multifaceted educational intervention on performing a narrative doctor-patient dialogue reflecting treatment targets and priorities of the patient and on performing a narrative patient-centred medication review. During the one year intervention GPs will have a total of three conversations à 30 minutes with the enrolled patients. Control: Care as usual. Follow-up per patient: 14 months after baseline interview. Primary efficacy endpoints: Differences in medication intake and health related quality of life between baseline and follow-up in the intervention compared to the control group. Randomization: Computer-generated by an independent institute. It will be performed successively when patient recruitment in the respective surgery is finished. Blinding: Participants (GPs and patients) will not be blinded to their assignment but will be unaware of the study hypotheses or outcome measures. DISCUSSION: There is growing evidence that the phenomenon of polypharmacy and low quality of drug use is substantially due to mis-communication (or non-communication) in the doctor patient interaction. We assume that the number of pharmaceutical agents taken can be reduced by a communicational intervention and that this will not impair the patients’ health-related quality of life. Improving communication is a core issue of future interventions, especially for patients with multimorbidity. TRIAL REGISTRATION: Current Controlled Trials ISRCTN46272088.